KEDUDUKAN OTONOMI DAERAH SEBAGAI PERAN DALAM PEMBANGUNAN EKONOMI - Adrian Hoirul Iqsan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Development is a process of growth and change for the better. All development is aimed at improving people's welfare. Economic development is an effort to increase a country's total income and per capita income by tracking population growth. This research method uses qualitative methods, which specifically analyze and describe the relationship between regional autonomy and economic growth in Indonesia. Regional autonomy plays an important role in economic development, with good and correct implementation, development can be achieved optimally. Therefore, regional development is expected to have a positive impact on economic growth.